PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. JAKARTA TEKNOLOGI UTAMA PEKANBARU - Norman Effendy; Machasin '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to identify and analyze the influence of the work environment, motivation and competence partially and simultaneously on the performance of employees of PT. Main tekologi Jakarta Pekanbaru. The subjects were all employees in the PT. Jakarta Pekanbaru Main Technology in 2014, amounting to 47 people. Using census sampling method and the data obtained is processed by multiple linear regression models (multiple regression) using SPSS 16 for Windows. Partial test results indicate that the work environment have a significant effect on performance; motivation significant effect on performance; and competence have a significant effect on performance. Results of environmental testing work, motivation, and competence simultaneously show the effect on the performance of 85.80% and the remaining 14.20% is influenced by other factors. The author suggests for the leadership of the company to further improve the working environment and pay attention, motivation and competence as significant influence on employee performance.Keywords: Performance, Work Environment, Motivation, Competence